The Role of the ASSURE Model in Indonesian and District Learning Planning - Ni Putu Diana Sari; I Gusti Ayu Maritati; Putu Suwidnyana; I Nyoman Sudiana (Bulletin of Science Education, 2024)
This research aims to describe the role of the ASSURE Model in designing Indonesian and regional language learning. This concerns designing Indonesian language learning that is effective, innovative, and comprehensive. It is hoped that the results of this research can expand the body of knowledge about the role of the ASSURE model in designing language learning, namely Indonesian and regional. The implementation of this research is based on the use of a method as an operational basis. Related to this are (1) a research design using qualitative descriptive, (2) types of research data related to research subjects and objects, (3) data collection methods using library study methods with research instruments in the form of written sources, and (4) data analysis methods such as data reduction, classification, description, and conclusion. data. The results of the research show that the role of the ASSURE model in designing Indonesian and regional language learning includes aspects (1) of conception, namely cognition and integrity of the model. In line with that, (2) relevance concerns the contribution of the ASSURE model in designing meaningful and sustainable Indonesian and regional language learning.